Frequência de doenças infecciosas e avaliação da resposta imune celular e humoral em adultos não tratados com deficiência congênita e isolada de GH - Almeida, Viviane Correia Campos (2016)
GH is important for the development and function of the immune system, but there is controversy on whether GH deficiency (GHD) is associated to immune disorders. A model of isolated GHD (IGHD), without others deficits or hormones replacement, may exclude if the lack of GH is associated with increased susceptibility to infections or with an altered responsiveness of the immune response. Our objective was to study the frequency of infectious diseases and the cellular and humoral immune response in adults with congenital, untreated IGHD. The study was performed in two steps: in the first, a cross-sectional study, 35 adults IGHD due to a homozygous mutation in the GHRH receptor gene and 31 controls were submitted to a clinical questionnaire to evaluate past and current history of infectious diseases, physical examination, and serology for tripanosomiasis, leishmaniasis, HIV, tetanus, hepatitis B and C. The only exclusion criterion for this first step was age less than 20 years old. In the second step, a study of cases with a control group for comparison of immune cellular and humoral response between the groups. The exclusion criteria were age less than 20 and more than 65 years old; diagnosis of HIV, infection or acute diseases; history of malignancies; autoimmune diseases; glucocorticoid and anti-allergic medications use; or current pregnancy. The immune response was evaluated in a subset of these subjects by serum total IgG, IgM, IgE and IgA measurement, skin tests (Protein Purified Derived (PPD), streptokinase and candidin), and response to vaccination for hepatitis B and tetanus (in individuals with negative serology), and to bacillus Calmette-Guérin (BCG) in subjects nonreactive to PPD. There was no difference between the groups in history of infectious diseases and baseline serologic data. IGHD subjects had lower total IgG, but within normal range, and a smaller induration diameter in streptokinase skin test, but no difference in the frequency of positivity to streptokinase (IGHD 2 in 21; controls 5 in 20). There was no difference in the positivity to PPD (IGHD 4 in 24; controls 10 in 28) and to candidin (IGHD 3 in 21; controls 1 in 19), or in the response to any of the vaccinations between the groups. The controls had a higher frequency of one positive skin test. In conclusion, adult untreated IGHD did not present an increased frequency of infections or significant alterations in the immunological tests, but we found lower total IgG levels and lower positivity to at least one skin test, without detectable clinical impact.